Haplotype Diversity of Partial Cytochrome b Gene in Kebumen Ongole Grade Cattle - T. Hartatik; D. Maharani; J. H. P. Sidadolog; A. Fathoni; Sumadi Sumadi (Tropical Animal Science Journal, 2018)
Cytochrome b gene is commonly used to figure out the genetic variation in animals. This research was designed to explore specific markers of Kebumen Ongole grade cattle and to understand the relationship between Kebumen and Brahman cattle using mtDNA cyt b sequences. The sequence of mtDNA cytochrome b gene of 14 individuals Kebumen Ongole grade cattle and 15 individuals  Brahman cattle was determined by using polymerase chain reaction and sequencing with a pair of primer. The haploview software was utilized to linkage disequilibrium (LD) analysis. As a result, 36 SNPs (single nucleotide polymorphisms) with 8 haplotypes were identified in Kebumen Ongole grade cattle. In contrast, a small number of SNPs (7) and haplotypes (6) were observed in Brahman cattle. The homozigosity in Brahman cattle was  higher than that in Kebumen Ongole grade cattle cattle. Moreover, based on mtDNA sequences, 50% of Kebumen Ongole grade cattle had 85% similarity with Brahman cattle. The SNP number and LD values of Kebumen Ongole grade cattle were greater than those of Brahman cattle. It was presumed that Brahman cattle might be introduced into Kebumen territory. In conclusion, some of Kebumen Ongole grade cattle have genetic relation with Brahman cattle. In addition, the information of SNP and haplotype results from this research can be used as markers to differentiate breeds of animals.